Financial Reporting of Intangible Assets: The Realibility of Measurement Methods - Lau, Chee Kwong (2008)
Intangible resources have become increasingly important since the 1990s and most of the major world economies have shifted their focus to become knowledge-based economies. Consequently, many researchers are questioning the decision usefulness of information contained in financial statements. Failure to report the substance of intangible resources has been identified as one of the major root causes. The existing asset recognition criteria, which emphasize measurement reliability has made it difficult for most of the intangible resources to be recognized as assets in the balance sheets. Based on the fact that measurement reliability is an issue in the recognition of intangible assets in financial reporting, this study asks the question: whether the estimated fair values of intangible assets derived from the selected measurement methods, faithfully represent the market value of the assets. This study aims to analyze the reliability of the selected measurement methods used in estimating the fair value of intangible assets. This study adopts the price model used in the relevant literature as the basis for theoretical framework. Fair values of intangible assets estimated using the selected measurement methods have been used to study their association with market values. Coefficient of correlation, coefficient of slope and coefficient of determination are employed to ascertain the significance and degree of representational faithfulness, which serves as a proxy to measurement reliability. This study finds that measurement methods based on abnormal cash flow and earnings produced fair value of intangible assets: which are representational faithful to their respective market values. This provides empirical evidence that the measurement methods are reliable in estimating the fair value of intangible assets. This study concludes that measurement reliability, via its proxy - representational faithfulness, is market verifiable and need not necessarily be mutually exclusive with relevance, which is another qualitative characteristic of decision usefulness. The findings and conclusions are vital in supporting the pervasive use of fair value measurement in financial reporting. This will eventually improve the quality of financial reporting of intangible assets and decision usefulness of accounting information. In a more recent development, the International Accounting Standards Board proposes to replace measurement reliability with representational faithfulness as a qualitative characteristic of decision useful information.